Argumen kesetaraan gender - Perspektif Al-Quran: satu ulasan - Muhammad Bukhari Lubis, (Universiti Kebangsaan Malaysia, 2006)
This is a review of a book on gender and sexuality from the perspective of Islam. The author brings up two main issues on the relationship between men and women and argues that biological sex differences should not equate domination of one sex over the other. Instead, biological differences make possible for love between the two to blossom (mawaddah wa rahmah) because each gender has his or her own roles to play which complement each other